Sugammadex Versus Neostigmine for Recovery of Respiratory Muscle Strength Measured by Ultrasonography in the Postextubation Period: A Randomized Controlled Trial. (24th October 2022) - Huang, Chanyan; Wang, Xuan; Gao, Shaowei; Luo, Wei; Zhao, Xu; Zhou, Qian; Huang, Wenqi; Xiao, Ying
Abstract : BACKGROUND: Although sugammadex is well known for its use in reducing the incidence of residual neuromuscular blockade, this has not always been translated to improved clinical measures of postoperative respiratory muscle strength. Expiratory muscles play an important role in airway clearance and inspiratory muscle capacity augmentation, yet they have not been well studied. Therefore, we tested the hypothesis on whether sugammadex could enhance expiratory muscle strength recovery more completely than neostigmine in the immediate postextubation period. METHODS: Adult patients having microlaryngeal surgery under total intravenous anesthesia were randomized to receive sugammadex or neostigmine. The thickening fraction of internal oblique abdominal muscle (TFIO ) and diaphragm excursion, respectively, reflecting expiratory and inspiratory muscle strength, were measured via ultrasonography at 3 time points: before induction (baseline), train-of-four ratio (TOFR) recovery to 0.9, and 30 minutes after postanesthesia care unit (PACU) arrival. The primary outcome was the change in TFIO from baseline to TOFR ≥0.9. The postoperative changes of diaphragm excursion from baseline, incidences of TFIO and diaphragm excursion returning to baseline levels, and the time from TOFR 0.9 to 0.95 and 1 were also measured. RESULTS: Among 58 patients, a significant difference in the change in TFIO from baseline to TOFR ≥0.9 between the sugammadex and neostigmine groups was observed: mean ± standard deviation, 9% ± 6% vs 16% ± 9%; difference in means: −6% (95% confidence interval [CI], −10 to −2); and adjusted P =.005 (adjusting for imbalanced variables between 2 groups). Sugammadex resulted in smaller changes in diaphragm excursion from baseline to TOFR ≥0.9 compared with neostigmine: difference in means: −0.83 cm (99.4% CI, −1.39 to −0.28 cm; Bonferroni-corrected P < .001). After 30 minutes in the postanesthesia care unit (PACU), 33% of patients reversed with sugammadex versus 14% of those receiving neostigmine reached baseline TFIO levels (99.4% CI, −14 to 52; Bonferroni-corrected P > .999). The incidences of TFIO and diaphragm excursion returning to baseline were relatively low (<40%) in both groups despite TOFR reaching 1. The median time from TOFR of 0.9 to 0.95 and to 1 among patients receiving sugammadex was 7 and 10× faster than those receiving neostigmine (0.3 vs 2 minutes, Bonferroni-corrected P = .003; 0.5 vs 5.3 minutes, Bonferroni-corrected P < .001, respectively). CONCLUSIONS: Sugammadex provides a more complete recovery of expiratory muscle strength than neostigmine at TOFR ≥0.9. Our data suggest that the respiratory muscle strength might still be impaired despite TOFR reaching 1.